2019
DOI: 10.1080/23288604.2019.1663646
|View full text |Cite
|
Sign up to set email alerts
|

International Funding for Global Common Goods for Health: An Analysis Using the Creditor Reporting System and G-FINDER Databases

Abstract: West Africa's Ebola epidemic of 2014-2016 exposed, among other problems, the under-funding of transnational global health activities known as global common goods for health (CGH), global functions such as pandemic preparedness and research and development (R&D) for neglected diseases. To mobilize sustainable funding for global CGH, it is critical first to understand existing financing flowing to different types of global CGH. In this study, we estimate trends in international spending for global CGH in 2013, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…In a study commissioned by the WHO for this series on financing global CGH, Schäferhoff and colleagues used the taxonomy shown in Table 2 to analyze ODA for health in 2013, 2015, and 2017 (the latest year for which data are available). 3 They found that the proportion of total ODA directed at global functions was only 23% in 2013, rising to 29% in 2015, and then falling again to 24% in 2017 ( Figure 1). In absolute terms, this means that international funding for global functions increased between 2013 and 2015 by 1.35 billion USD, bringing funding for global functions to a total of 7.3 billion USD in 2015, and then fell by 300 million USD to 7.0 billion USD in 2017.…”
Section: How Much Is the World Spending On Global Functions?mentioning
confidence: 96%
See 1 more Smart Citation
“…In a study commissioned by the WHO for this series on financing global CGH, Schäferhoff and colleagues used the taxonomy shown in Table 2 to analyze ODA for health in 2013, 2015, and 2017 (the latest year for which data are available). 3 They found that the proportion of total ODA directed at global functions was only 23% in 2013, rising to 29% in 2015, and then falling again to 24% in 2017 ( Figure 1). In absolute terms, this means that international funding for global functions increased between 2013 and 2015 by 1.35 billion USD, bringing funding for global functions to a total of 7.3 billion USD in 2015, and then fell by 300 million USD to 7.0 billion USD in 2017.…”
Section: How Much Is the World Spending On Global Functions?mentioning
confidence: 96%
“…2 (Flows of ODA to global functions in recent years are the focus of a related paper in this special issue. 3 ) Our paper focuses on the role of ODA in supporting global functions. The CIH made a key distinction between development assistance for health (DAH) that supports global functions, bringing transnational (regional or global) benefits, and DAH that is given to an individual country to support disease control activities (e.g., reducing maternal mortality) in that country alone.…”
mentioning
confidence: 99%
“…Building off the paper by Yamey and colleagues, Schäferhoff, Chodavadia, Martinez, Kennedy McDade, Fewer, Silva, Jamison, and Yamey present "International Funding for Global Common Goods for Health: An Analysis Using the Creditor Reporting System and G-FINDER Databases." 44 This article estimates expenditure trends in international financing for global CGH between 2013 and 2017 to gauge their prioritization in the global health funding agenda. The time period covers before, during, and after the 2014-2016 Ebola epidemic.…”
Section: Finding Our Way Back To Basicsmentioning
confidence: 99%
“…The first articles in this series discuss the "what," defining CGH and providing the conceptual foundation for the definition. 4,6 Subsequent papers focus on how to finance and provide CGH, 5,7,8 with focused discussions on health emergency and disaster risk management 9 and on environmental issues. 10 Commentaries and case examples highlight some challenges to financing CGH, but also present effective approaches that have been taken to prioritizing financing for CGH.…”
Section: Developing the Case For Cghmentioning
confidence: 99%
“…Yamey et al 5 consider CGH that require financing and action at the global level, including sustainable global mechanisms and targeted resource mobilization efforts, pooled funding, and strategic purchasing. Schäferhoff et al 8 provide empirical evidence by tracking expenditures to global CGH in recent years. Their analysis shows that increases in funding following the Ebola crisis have already begun to show a decreasing trend.…”
Section: Developing the Case For Cghmentioning
confidence: 99%